A technical solution to a professional problem: The risk management functions of prognosticators in the context of prognostication post-cardiac arrest - Field-Richards, Sarah Elizabeth; Timmons, Stephen (Frontiers in Sociology, 2022)
Cardiac arrest (CA) is a major cause of mortality and morbidity globally. Two-thirds of deaths among patients admitted to Intensive Care Units following out-of-hospital CA are due to neurological injury, with most as a consequence of withdrawing life-sustaining treatment, following prognostication of unfavourable neurological outcome. Given the ramifications of prognosis for patient outcome, post-cardiac arrest (P-CA) guidelines stress the importance of minimising the risk of falsely pessimistic predictions. Although prognosticator use is advocated to this end, 100% accurate prognosticators remain elusive, therefore prognostication P-CA remains pervaded by uncertainty and risk. Bioethical discourse notwithstanding, when located within a wider socio-cultural context, prognostication can be seen to present risk and uncertainty challenges of a professional nature. Such challenges do not however, subvert the medical professions’ moral and ethical prognostication obligation. We interpret prognosticator use as an attempt to manage professional risk presented by prognostication P-CA, and demonstrate how through performing ‘risk work’, prognosticators serve professional functions, mediating tension between the professional duty to prognosticate, and risk presented. We draw on sociological analyses of risk and uncertainty, and the professions, to explicate these (hitherto less enunciated) professional risk management functions of prognosticators. Accordingly, use of prognosticators is conceived of as a professional response – a technical/scientific solution to the problem of professional risk, inherent within the P-CA prognostication process.